"Brick-and-mortar" sandwiched porous carbon building constructed by metal-organic framework and graphene: Ultrafast charge/discharge rate up to 2 V s−1 for supercapacitors. (December 2016) - Wang, Lan; Wei, Tong; Sheng, Lizhi; Jiang, Lili; Wu, Xiaoliang; Zhou, Qihang; Yuan, Bao; Yue, Jingming; Liu, Zheng; Fan, Zhuangjun
Abstract: Supercapacitors based on microporous carbons face some contradictory and competitive challenges such as relatively high specific capacitance and low charge rates. Previously, the mesopores in these carbons can effectively enhance the ion transport, but their charge and discharge rates are often less than 1 V s −1 . Here, we have demonstrated "brick-and-mortar" sandwiched porous carbon building by using MOF-5 derived porous carbon film as "mortar" and the graphene nanosheet as "brick". The confined mesoporous channels between-in graphene sheets provide efficient ion transport pathways for fast ion diffusion, and the existence of graphene can effectively maintain the conductivity and structural stability of the carbon building. As a result, the obtained porous carbon building exhibits fast frequency response with an ultrahigh rate up to 2 V s −1, high specific capacitance of 345 F g −1 at 2 mV s −1, and outstanding cycling stability of 99% capacitance retention after 10, 000 cycles. More importantly, the as-assembled symmetric supercapacitor in aqueous electrolyte can deliver a high energy density of 30.3 Wh kg −1 at a power density of 137 W kg –1 and superior cycling life (94% capacitance retention after 10, 000 cycles). Even at a high power density of 11.9 kW kg –1, it still remains an energy density of 10.6 Wh kg –1, higher than those of previously reported carbon-based symmetric supercapacitors and other asymmetric supercapacitors. Graphical abstract: The "brick-and-mortar" sandwiched porous carbon building (C-GMOF) was fabricated by using MOF-5 derived porous carbon film as "mortar" and graphene nanosheet as "brick". As a result, the C-GMOF exhibits excellent frequency response with charge/discharge rate up to 2 V s −1, high specific capacitance of 345 F g −1, high energy density and outstanding cycling stability. Highlights: "Brick-and-mortar" sandwiched porous carbon building provides highly efficient ion/electron transport pathways and structural stability for the electrode. The porous carbon building shows an ultrahigh charge/discharge rate up to 2 V s −1, high specific capacitance and outstanding cycling stability. The as-assembled symmetric supercapacitor delivers high-energy storage even at high power densities.